Functional Switch From Pro-Neurotrophins to Mature Neurotrophins - Sun, Xiao-Long; Chen, Bei-Yu; Xia, Yi; Wang, Jing-Jie; Chen, Liang-Wei (Current Protein and Peptide Science, 2013)
Growing evidence has shown that the proforms of several neurotrophins, e.g., nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin3 (NT3) can be synthesized, secreted from neurons or glial cells and function actively in mammalian nervous system. By the intracellular and extracellular enzymatic cleavage processing, mature neurotrophins are generated and exert their functions in the developing, physiological and pathological activities. While mature neurotrophins exhibit neuroprotective roles via tyrosine kinase receptors (TrkA, TrkB and TrkC), the proforms of neurotrophins show totally-different biological effects that may induce apoptotic cell death of neurons by triggering p75NTR-sortilin signaling cascades. In addition, another key neurotrophic factor named glial-derived neurotrophic factor (GDNF) also appears to be a product generated from proGDNF, and its cleavage and potential biological function of proGDNF remains an unrevealed problem. Obviously, accumulating studies indicated that the exact or timely cleavage processing should be essential for the functional switch from proneurotrophins to mature neurotrophins, while dysfunction in the enzymatic cleavage, aberrant extracellular release, and abnormal subunit organization of binding receptors might be also crucially involved in neurodegeneration of the central neurons, pathogenesis, and even disease progression of various neurodegenerative diseases in human beings.
Keywords: Neurotrophins